A wideband accurate compact 6‐bit phase shifter in 0.15‐μm GaAs technology. Issue 2 (12th November 2022) - Zeng, Jialong; Xie, Chunshuang; Zhang, Desheng; Feng, Jie; Tan, Cheng; Yu, Zhongjun
Abstract: A Ku wideband accurate compact 6‐bit digital phase shifter is designed in this letter using three different switched phase shift structures: the switched L/C structure, T‐type structure, and high‐pass/low‐pass network. To improve the bandwidth and the gain flatness, an improved switched L/C structure is used and the systematic cascade sequence of the phase shifter is optimized. The improved switched L/C structure solves the problem that conventional L/C networks are hypersensitive to the coupling capacitance at high‐frequency input. As a result, the improved L/C structure can achieve wideband and better s‐parameters. The proposed 6‐bit switched phase shifter is implemented in 0.15‐μm GaAs pHEMT process. The measured root‐mean‐square (rms) phase error is less than 2.8° at 12–18 GHz, and the average insertion loss (IL) is 6.5–6.9 dB. The chip size of the proposed 6‐bit digital phase shifter is 3.1 × 1 mm 2, including all RF and dc pads, which is very suitable for radar systems.